The Ability of Tetrahymena utriculariae (Ciliophora, Oligohymenophorea) to Colonize Traps of Different Species of Aquatic Carnivorous Utricularia - Sirová, Dagmara; Kreidlová, Veronika; Adamec, Lubomír; Vrba, Jaroslav (The Journal of eukaryotic microbiology, 2020)
The host specificity of the recently described ciliate species Tetrahymena utriculariae was tested in a greenhouse growth experiment, which included 14 different species of aquatic Utricularia as potential host plants. We confirmed the high specificity of the interaction between U. reflexa and T. utriculariae, the former being the only tested host species able to maintain colonization for prolonged time periods. We conclude that this plant-microbe relationship is a unique and specialized form of digestive mutualism and the plant-microbe unit a suitable experimental system for future ecophysiological studies.
Keywords: symbióza; Tetrahymena; Lamiales; Affinity; rootless plant; sterile traps; zoochlorellae; Symbiosis; colonization; hluchavkotvaré; trap fluid; ciliate; Host-Parasite Interactions; long-term survival; Utricularia reflexa; interakce hostitele a parazita; Carnivory; masožravci